1987
DOI: 10.1139/v87-178
|View full text |Cite
|
Sign up to set email alerts
|

Pulse cyclic voltammetry. I. Static solutions

Abstract: This paper is dedicated to Professor Douglas E. Ryan on the occasio~l of his 65th birthdayGORDON N. ECCLES and WILLIAM C. PURDY. Can. J. Chem. 65, 105 1 (1987).By using pulse cyclic voltammetry rather than cyclic voltammetry at a relatively high scan rate, an increase in sensitivity and a lowering of the detection limit by more than a factor of two are demonstrated for the ferricyanide-ferrocyanide couple at a carbon electrode. The test for reversibility based on peak shape or symmetry comparison is enhanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…In static solutions it was found that the residual current becomes reproducible after completion of the first cycle during a multiple scan CV (16). This behaviour is also observed in flowing streams and is illustrated by the results of a multiple scan CV of a 20 pL injection of 1 mM quinone in 1 M sulfuric acid shown in Fig.…”
Section: Fia Of Quinone Using a Rapid Scan CV And Pcv Detectorsupporting
confidence: 56%
See 1 more Smart Citation
“…In static solutions it was found that the residual current becomes reproducible after completion of the first cycle during a multiple scan CV (16). This behaviour is also observed in flowing streams and is illustrated by the results of a multiple scan CV of a 20 pL injection of 1 mM quinone in 1 M sulfuric acid shown in Fig.…”
Section: Fia Of Quinone Using a Rapid Scan CV And Pcv Detectorsupporting
confidence: 56%
“…In spite of this disadvantage, a wealth of voltammetric information can be obtained by applying a pulse cyclic voltammetric waveform as the excitation signal (15,16). This work will show some of the merits achieved when applying this waveform to an LTIC electrode in flow-injection analysis (FlA) using the hydroquinone-quinone couple.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we explore a composite waveform for the evaluation and identification of electron transfer mechanisms, i.e., cyclic square wave voltammetry. , This waveform utilizes a square wave which steps through the region of the formal potential of the electroactive species under study in two directions. Although there is strong literature precedent for cyclic pulse techniques, only a few reports on CSWV have appeared. ,,,− We believe the use of this waveform merits consideration for several reasons. First, the utilization of the square wave potential waveform and the discrete current sampling regimen will permit mechanistic evaluations at trace levels.…”
mentioning
confidence: 99%
“…9,10 This waveform utilizes a square wave which steps through the region of the formal potential of the electroactive species under study in two directions. Although there is strong literature precedent for cyclic pulse techniques, [11][12][13][14][15][16][17] only a few reports on CSWV have appeared. 9,10,16,[18][19][20][21][22][23][24][25][26][27][28] the use of this waveform merits consideration for several reasons.…”
mentioning
confidence: 99%